Short-term tibolone does not interfere with endothelial function: a double-blinded, randomized, controlled trial. (3rd May 2016) - Celani, M. F. S.; Hurtado, R.; Brandão, A. H. F.; Maciel da Fonseca, A. M. R.; Geber, S.
ABSTRACT: Objective To evaluate the effect of short-term hormone replacement therapy with tibolone 2.5 mg daily on endothelial function of healthy postmenopausal women, using flow-mediated dilation (FMD) of the brachial artery. Methods We performed a randomized, double-blinded, placebo-controlled study. A total of 100 healthy postmenopausal women were randomly allocated to receive tibolone ( n  = 50) or placebo ( n  = 50) for 28 days. Measurement of the FMD of the brachial artery was performed before and after the use of tibolone and placebo. Results A total of 31 women completed the study in the tibolone group, and 32 women completed the study in the control group. The results of the FMD measurements obtained from the women in the two groups before treatment were similar (0.018 and 0.091, for tibolone and placebo, p  = 0.57). The values of the FMD in women who used tibolone and placebo, before and after the treatment, were similar in both groups. The numbers of women who presented an increase in the values of the FMD in both groups were also similar. Conclusion Our results demonstrate that the administration of 2.5 mg tibolone to healthy postmenopausal women for 28 days does not promote endothelial-dependent vasodilation, measured by FMD of the brachial artery.